Transcranial direct current stimulation regulates phenotypic transformation of microglia to relieve neuropathic pain induced by spinal cord injury - Tan, Mingliang; Feng, Zhou; Chen, Hui; Min, Lingxia; Wen, Huizhong; Liu, Hongliang; Hou, Jingming (Frontiers in Behavioral Neuroscience, 2023)
Objective: Neuropathic pain is a common complication after spinal cord injury (SCI). Transcranial direct current stimulation (tDCS) has been confirmed to be effective in relieving neuropathic pain in patients with SCI. The aim of this study is to investigate the effect of tDCS on neuropathic pain induced by SCI and its underling mechanism. Materials and Methods: The SCI model was induced by a clip-compression injury and tDCS stimulation was performed for two courses (5 days/each). The motor function was evaluated by Basso-Beattie-Bresnahan (BBB) score, and the thermal withdrawal threshold was evaluated by the thermal radiation method. The effects of tDCS on the cerebral cortex, thalamus, midbrain, and medulla were detected by the enzyme-linked immunosorbent assay (ELISA) and immunofluorescence. Results: The results showed that SCI reduced the thermal withdrawal threshold and increased the concentration of inflammatory cytokines in the cortex, thalamus, midbrain, and medulla, including the tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6). In addition, the activation of microglia and the proportion of M1 phenotypic polarization increased significantly in the ventral posterolateral (VPL), ventral tegmental (VTA), and periaqueductal gray (PAG) regions after SCI. After tDCS treatment, the thermal withdrawal threshold and motor function of SCI rats were significantly improved compared to the vehicle group. Meanwhile, tDCS effectively reduced the concentration of pro-inflammatory cytokines in the cortex, thalamus, midbrain, and medulla and increased the concentration of anti-inflammatory cytokines interleukin-10 (IL-10) in the thalamus. In addition, tDCS reduced the proportion of the M1 phenotype of microglia in VPL, VTA, and PAG regions and increase the proportion of the M2 phenotype. Conclusions: The results suggest that tDCS can effectively relieve SCI-induced neuropathic pain. Its mechanism may be related to regulating the inflammatory and anti-inflammatory cytokines in corresponding brain regions via promoting the phenotypic transformation of microglia.